Toxic waste - Stonebarger, Stone; Hawkhill Associates (Wisconsin : Hawkhill Associates, 2004)
Experts discuss the creation and disposal of toxic wastes and their environmental effects and helps in better understand the science of toxicology
Title from title screen
This dvd has special guided questions and mastery quizzes
Music, Michael Stonebarger ; graphics, Lin Haley, Dong Normington, Michael Stonebarger
Keywords: Hazardous wastes; Environmental toxicology; Pollutions